Menelusuri Jejak Ketaqwaan: Pendidikan Spiritual dalam Al-Quran - Junaidi, Kholid (Lembaga Anotero Scientific Pekanbaru, 2025)
The purpose of writing this scientific paper is to find out about Education in the Qur'an. The verses in the Qur'an are many storage of devotion education that provide very valuable lessons for life. Therefore, we must explore the progress or education of the verses of the Qur'an, so that if we are always pious to God by carrying out the commands and knowing His prohibition, surely he will give us furqan and cover the mistakes We are not being placed in the world and are covered in the hereafter so that God does not demand our responsibility, while humans demand our sins, will be given a change by God so that He is willing and we are fearing he will forgive Our sins.